Profile of Students' Environmental Literacy and the Needs of Science Teaching Materials Integrated with the Local Potential of Rawa Bento Based on Problem Based Learning - Aditya Fahlevi*; Zuhdan Kun Prasetyo; Suyanta Suyanta; Sabar Nurohman; Sri Rejeki Dwi Astuti (Universitas Syiah Kuala, 2023)
The achievement of environmental literacy of students in Indonesia still faces various problems. Even though environmental literacy is one of the important literacy for students to have. This study aims to determine the profile of environmental literacy among junior high school students and the need for integrated science teaching materials based on problem based learning (PBL) at Rawa Bento. The population of this study consists of junior high school students from six schools in Kerinci Regency. The research sample includes 90 students selected using a purposive random sampling technique. Data collection is conducted through instruments such as tests to measure environmental literacy and student response questionnaires to determine the need for integrated science teaching materials based on PBL at Rawa Bento. The data in the study are analyzed using quantitative descriptive analysis techniques. The research findings are as follows: 1) the majority of students have low to moderate levels of environmental literacy. 38.9% of students still have a low level of environmental literacy, 54.4% fall into the moderate category, and only 6.7% are in the high category; 2) the lowest ability of students is in analyzing the impacts resulting from environmental issues; 3) there is a need for the development of integrated electronic teaching materials based on PBL at Rawa Bento to enhance students' environmental literacy. Based on the results of the study, it can be concluded that the environmental literacy of students from six schools in Kerinci Regency is in the medium category